A minimally invasive marine mammal sex determination method using epidermal tissue recovered from suction-cup tags - Sadie X. Novak; Jacob M.J. Linsky; Kaitlyn J. Knapp; Susan E. Parks; David Wiley; Dana A. Cusano (PLoS ONE, 2025)
For many baleen whales, minimal sexual dimorphism means that sex cannot necessarily be reliably determined through observation alone. Suction cup tags deployed for behavioral studies of free-ranging whales sometimes retain exfoliated epidermal tissue from the tagged animal that can potentially be used for molecular genetic sexing. This study provides a protocol to recover and preserve skin from suction cup tags and compares the accuracy of resulting PCR-based sex determinations relative to independent data on individual sex. Skin samples (N = 43) were recovered from tags deployed on North Atlantic humpback and right whales of known sex. Of these, data were obtained from 21 tags deployed on 15 individuals. A PCR-based sex determination yielded correct results for 9 male and 11 female samples. One female was misidentified as male in one of two samples collected from the same tag, suggesting the potential for sexing error based on suction cup tag-derived tissue. The probability of accurate results given current information was estimated using Bayes theorem, with a female result estimated to be 100% reliable, and a male result estimated to be 91% reliable. The minimum DNA yield that resulted in a successful PCR run was 29 ng, however four samples with higher DNA yield did not. With further work, this protocol may increase the reliable data that can be collected as part of suction-cup tagging studies of cetaceans.